Exploration of nyamplung rizosphere nitrogen fixing bacteria in mine reclamation - Sriwulan Sriwulan; Tita Dewi Fitriani; Nadia Puspita Maya; Ni'matur Rohmah; Eko Purnomo (Bioeksperimen: Jurnal Penelitian Biologi, 2024)
Nitrogen fixing bacteria have the ability to utilize free nitrogen as a nitrogen source for their growth. These bacteria are able to make efficient availability of N- in the soil, so that it can be utilized by plants. The aim of this study was to obtain nitrogen fixing bacteria isolates from the rhizosphere of nyamplung plants in limestone reclamation lands. Isolation and testing of nitrogen fixation ability by nitrogen fixing bacteria was carried out using selective Ashby's Mannitol Agar media. The isolation results obtained 5 isolates on Ashby's Mannitol Agar media. The morphological characters of the colonies of the five isolates showed round and irregular shapes, flat and convex elevations with flat edges, white, cloudy white and clear. Microscopic observation showed that the isolates consisted of gram-positive and negative bacteria with bacilli cell shape. The catalase test showed 4 positive isolates and 1 negative. The conclusion of this study was that 5 nitrogen fixing bacteria isolates were obtained from the rhizosphere of the nyamplung limestone land plant. Isolates 1, 3, and 5 showed the character of the genus Clostridium, isolate 2 led to the genus Bacillus, and isolate 4 had the same character as the genus Klabsiella.